Analisis Faktor-Faktor yang Mempengaruhi Minat Konsumen untuk Menggunakan OVO di Indonesia - Mochamad Malik Akbar Rohandi; Elvira Azis; Roid Sadad (Universitas Islam Bandung, 2020)
AbstractThe model factors influencing consumer’s intention to use e-payment system with the addition of culture variables and perceived security variables is the model used in this study. The EFA factor analysis method is used to test a predetermined model. The sample of this study was 100 OVO users from various provinces in Indonesia as respondents from questionnaires distributed online. Based on the results of the study it was found that the variable culture, perceived security, performance expectance, and effort expectance did not affect the electronic payment system's intention to use, while the social influence had an effect on the electronic payment system's intention to use.Keywords: EFA, consumer’s intention, e-payment system, OVO.